ANALISIS BEBAN KERJA BIDAN DESA DI PUSKESMAS DUREN KABUPATEN SEMARANG - Kartika Yufi Aruming Melati; Putri Asmita Wigati; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Village midwife is health worker that is needed as part of Mother and Child Program. The result of preliminary survey on 3 village midwives at Duren Public Health Centre showed that the workload of village midwife was heavy, because besides performing their main duty, those village midwives also responsible for healthcare services as a whole, starting from general medications, communicable disease surveillances, nutrition services, and sputum taking services. This caused few scope targets could not be fulfiled Duren Public Health Center target yet. This research was intended to analyze village midwives workload at Duren Public Health Center in Semarang District. Research population was village midwives workhour at Duren Public Health Center. Samples taken were 2250 minutes or 37,5 hours for a single village midwife in 6 days. Research subjects were 4 village midwives. Research type was descriptive, work sampling method at work hour and daily log method at outside work hour. Then performed data processing and analyzing. Results of the research showed that the most performed type of activity done by village midwives at Duren Public Health Center was main activity of Mother and Child Health recording and reporting. Average productive time of village midwives at Puskemas Duren in 6 days was 82,94% which exceeded established standard 75%, and non productive time of village midwives was 17,05%, still below established standard, which is 25%. Therefore village midwifes workload at Duren Public Health Center at workhour was heavy because the acerage workload was 1866.3 minutes, which exceeded effective time in 6 days, 1680 minutes. Workload pattern of village midwives tend to do main and additional activity outside Village Healthcare Polyclinics first in the morning, then performing main and additional activity inside Village Healthcare Polyclinics in the afternoon. It is suggested that Duren Public Health Center should review about main duty that needs to be done by village midwife.